GLAST (GLutamate and ASpartate Transporter) in human prefrontal cortex; interactome in healthy brains and the expression of GLAST in brains of chronic alcoholics. (May 2019) - Kashem, Mohammed Abul; Sultana, Nilufa; Pow, David V.; Balcar, Vladimir J.
Abstract: We have analysed post-mortem samples of prefrontal cortex from control and alcoholic human brains by the technique of Western blotting to estimate and compare the expressions of glutamate transporter GLAST (Excitatory Amino Acid Transporter One; EAAT1). Furthermore, using the non-alcoholic prefrontal cortex and custom-made GLAST (EAAT1) antibody we determined GLAST (EAAT1) "interactome" i.e. the set of proteins selectively bound by GLAST (EAAT1). We found that GLAST (EAAT1) was significantly more abundant (about 1.6-fold) in the cortical tissue from alcoholic brains compared to that from non-alcoholic controls. The greatest increase in the level of GLAST (EAAT1) was found in plasma membrane fraction (2.2-fold). Additionally, using the prefrontal cortical tissue from control brains, we identified 38 proteins specifically interacting with GLAST (EAAT1). These can be classified as contributing to the cell structure (6 proteins; 16%), energy and general metabolism (18 proteins; 47%), neurotransmitter metabolism (three proteins; 8%), signalling (6 proteins: 16%), neurotransmitter storage/release at synapses (three proteins; 8%) and calcium buffering (two proteins; 5%). We discuss possible consequences of the increased expression of GLAST (EAAT1) in alcoholic brain tissue and whether or how this could disturb the function of the proteins potentially interacting with GLAST (EAAT1) in vivo. The data represent an extension of our previous proteomic and metabolomic studies of human alcoholism revealing another aspect of the complexity of changes imposed on brain by chronic long-term consumption of ethanol. Highlights: We studied glutamate transporter GLAST in human prefrontal cortex. GLAST expression was significantly increased in alcoholic brains. The increase in GLAST appeared to be most pronounced in plasma membranes. In healthy brains, we used proteomics to determine GLAST "interactome". GLAST interacted with 38 proteins; 18 of those were involved in energy metabolism.